ผลของการสอนโดยอ้อมตามแนวคิดของคาร์ล โรเจอร์ ที่มีต่อความมีเหตุผลบนพื้นฐานปรัชญาของเศรษฐกิจพอเพียงของเด็กอนุบาล - กัลยา จินดารัตน์ ฟราห์ม (จุฬาลงกรณ์มหาวิทยาลัย, 2011)
The purpose of this research was to study the effects of Carl Roger’s process of nondirective teaching on reasonableness based on the sufficiency economy philosophy of kindergarteners. The children observed in this research were evaluated based on three criteria: making intelligent and rational choices, self-reliance, and efficient and responsible use of resources. The sample used in this study included 60 children in Anuban 3, age 5 to 6 years, from Hua Dong Municipal School in Uttaradit. These children were divided into two groups of 30 children each, the experiment group and the control group. The experiment group was taught using the study’s method of combining Carl Rogers’ nondirective teaching method with Sufficiency Economy Philosophy. This was divided into a weekly routine of four steps. 1) Introducing a problem or situation for the children to consider, 2) allowing the children to develop potential solutions to the problem, 3) encourage the children to explain and justify their solutions, and 4) reviewing the problem and considering possible outcomes of the implementation of various solutions. The experiment group followed this plan for the 10- week duration of the experiment, while the control group followed their school’s normal course schedule. The data collected was analyzed by arithmetic mean, standard deviation, and t-test using SPSS software. The results showed that after the experiment, the children who were taught using the combined methods of Nondirective teaching and Sufficiency Economy Philosophy scored higher on a post-test to evaluate their ability levels in the three research criteria with a statistically significant difference at .01 levels.